2001
DOI: 10.2307/2696401
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patent Litigation: A Window on Competition

Abstract: We thank the editor, Rob Porter, and two anonymous referees for helpful suggestions. Dietmar Harhoff, Robert Merges, Suzanne Scotchmer and Brian Wright provided constructive comments on an earlier draft. We thank Derwent and Micro-Patent for access to their data and Orli Arav for assistance in obtaining them, Sam Kortum for the data on total patenting activity, and Jonathan Putnam for extracting the matched data set and the citations information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
407
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 681 publications
(429 citation statements)
references
References 27 publications
19
407
3
Order By: Relevance
“…Some scholars have suggested that a large number of citations to others implies that the particular innovation is likely to be more derivative in nature (Lanjouw and Schankerman 2004). This is more evident when citations are within the same technological field.…”
Section: Patent Quality Across Different Communitiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Some scholars have suggested that a large number of citations to others implies that the particular innovation is likely to be more derivative in nature (Lanjouw and Schankerman 2004). This is more evident when citations are within the same technological field.…”
Section: Patent Quality Across Different Communitiesmentioning
confidence: 98%
“…4 There is sufficient evidence in the literature that the economic value of patents is associated with the number and quality of citations received in other patents (Hall, Jaffe and Trajtenberg 2005;Harhoff et al 1999;Trajtenberg 2002). Harhoff et al (2003) and Lanjouw and Schankerman (2001) have suggested a different metrics, i.e. the existence of litigation for patents, implying that patents for which assignees are willing to pay for defence against infringement, have larger economic value.…”
Section: Literature Background On Science-technology Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Litigation behavior itself has been studied in several papers (Waldfogel 1995, Lanjouw and Lerner 1998, Lanjouw and Schankerman 2001, Marco 2005.…”
mentioning
confidence: 99%